Biphasic electropolymerization of polyaniline-multiwalled carbon nanotube nanocomposite - Srivastava M.; Kumar A.; Gupta B.; Srivastava S.K.; Prakash R. (My University, 2025)
Despite the tremendous research on conjugated polymers to date, polyaniline, PAni and its derivatives are the most interesting conjugated polymers due to their unique electrochemical properties, easy polymerization, low cost and wide range of application. In the recent years polymer composites formation with various nanofillers are explored to enhance the various properties of the polymers. Multi-walled carbon nanotube, MWNT is one of the well-known nanofillers for its excellent electrical, mechanical and thermal properties. Besides all properties, the processability, stability and solubility hinder its commercial utilization and fabrication of devices. To overcome these limitations, coating of PAni over MWNTs is one of the possible ways to obtain the high performance of the resulted nanocomposite towards device applications. Although various strategies have been developed to produce such nanocomposites (i.e. polymer supported by conducting templates) but still the homogeneity/uniformity of nanocomposite and stability are the major challenges. Though the electrochemical polymerization technique suffers from various limitations, it is still a good approach for the uniform and thin film formation. However, formation of composites is rather difficult as the fillers may not be electroactive and also may not form homogeneous suspension (or colloidal state) in the electrolytes in which monomers are dissolved. Therefore, the distribution of fillers in the polymer matrixes is difficult to control using conventional electrochemical methods. We proposed a biphasic electropolymerization method as an efficient approach for polymerization of monomers with nanofillers to get uniform and homogeneous polymercomposites. This technique not only provides a better selection of solvents for monomers and fillers but also better control of diffusion and kinetics. In this chapter, electrochemical techniques used for synthesis with the latest development in the electrochemical synthesis of PAni nanocomposite is described with our novel biphasic electropolymerization technique for multi-walled carbon nanotubepolyaniline (MWNT-PAni) nanocomposite. MWNT-PAni nanocomposite formation, based on the biphasic electropolymerization technique, provides a general method for the formation of uniform nanocomposites for other polymers and fillers. © 2013 by Nova Science Publishers, Inc. All rights reserved.